Proteomic analysis revealed the pharmacological mechanism of Xueshuantong injection in preventing early acute myocardial infarction injury - Wang, Aoao; Li, Ying; Wang, Ziyan; Xin, Gaojie; You, Yue; Sun, Mingqian; Miao, Lan; Li, Lei; Pan, Yinghong; Liu, Jianxun (Frontiers in Pharmacology, 2022)
Background: Acute myocardial infarction (AMI) is a common and life-threatening cardiovascular disease. However, there is a lack of pathology and drug studies on AMI within 20 min. Xueshuantong injection (XST) is mainly composed of Panax notoginseng saponins, which can dilate blood vessels and improve blood circulation, and is clinically used in the treatment of cardiovascular and cerebrovascular diseases. Purpose: The study aimed to investigate the protective mechanism of Xueshuantong injection against acute myocardial infarction within 20 min in rats by proteomic methods and molecular docking. Method: The male Sprague–Dawley rat acute myocardial infarction model was established by LAD ligation, and Xueshuantong injection (38 mg/kg) was injected into the caudal vein 15 min before surgery. Cardiac function evaluation, morphological observation, label-free quantitative proteomics, Western blotting analysis, molecular docking, and affinity measurement were applied in this study. Results: In a span of 20 min after acute myocardial infarction, the model group showed significant cardiac function impairment. Xueshuantong injection can significantly improve cardiac function and prevent pathological injury of myocardial tissue. A total of 117 vital differentially expressed proteins were identified by proteomic analysis, including 80 differentially expressed proteins (DEPs) in the sham group compared with model rats (Sham: model) and 43 DEPs in model rats compared with the Xueshuantong injection group (Model: XST). The treatment of Xueshuantong injection mainly involves “poly(A) RNA binding” and “cadherin binding involved in cell–cell adhesion.” The differentially expressed levels of the pathways related to proteins Echdc2, Gcdh, Dlst, and Nampt, as well as 14-3-3 family proteins Ywhaz and Ywhab, could be quantitatively confirmed by WB. Molecular docking analysis and SPR analysis revealed that Ywhaz has a generally stable binding with five Xueshuantong injection components. Conclusion: Xueshuantong injection (XST) could protect rat myocardial function injury against AMI in 20 min. Echdc2, Ywhaz, Gcdh, Ywhab, Nampt, and Dlst play an essential role in this protective effect. In particular, Ywhaz might be the core target of Xueshuantong injection when treating acute myocardial infarction in the early stage. This study promoted the understanding of the protective mechanism of Xueshuantong injection in 20 min injury of acute myocardial infarction and contributed to the identification of possible targets of Xueshuantong injection.